2020
DOI: 10.1007/978-3-030-59725-2_56
|View full text |Cite
|
Sign up to set email alerts
|

Cascaded Robust Learning at Imperfect Labels for Chest X-ray Segmentation

Abstract: The superior performance of CNN on medical image analysis heavily depends on the annotation quality, such as the number of labeled image, the source of image, and the expert experience. The annotation requires great expertise and labour. To deal with the high inter-rater variability, the study of imperfect label has great significance in medical image segmentation tasks. In this paper, we present a novel cascaded robust learning framework for chest X-ray segmentation with imperfect annotation. Our model consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…This further paves the way for development of AI detection and evaluation of cancer changes, such as temporal subtraction where the changes can be detected at different time intervals. Previous research also showed the superior performance of AI algorithms [ 2 , 3 , 4 ]. The registration of PET and MRI remains challenging for three reasons: (1) the patient position is different during PET and MR scanning.…”
Section: Introductionmentioning
confidence: 95%
“…This further paves the way for development of AI detection and evaluation of cancer changes, such as temporal subtraction where the changes can be detected at different time intervals. Previous research also showed the superior performance of AI algorithms [ 2 , 3 , 4 ]. The registration of PET and MRI remains challenging for three reasons: (1) the patient position is different during PET and MR scanning.…”
Section: Introductionmentioning
confidence: 95%
“…They trained the segmentation model on examples with clean annotations. For chest X-ray segmentation with imperfect labels, Xue et al [298] adopted a cascade strategy consisting of two stages: a sample selection stage, which selects the clean annotated examples as the co-teaching paradigm, and a label correction and model learning stage, which learns the segmentation model from both the corrected labels and original labels. To segment skin lesions from noisy annotations, Mirikharaji et al [299] adopted a spatially adaptive reweighting approach to emphasize the learning from clean labels and reduce the side effect of noisy pixel-level annotations.…”
Section: A Learning From Noisy Labelsmentioning
confidence: 99%
“…To analyze and address various kinds of label errors, an important thing is to construct large scale datasets with real noises, which in itself is a challenging task. Currently, most studies still use public datasets with simulated label perturbations [284], [298], [301] or private datasets [25], [300]. Building up public benchmarks with real noises is crucial to make further breakthroughs, especially for clinical usage.…”
Section: E Complex Label Noises Are Challengingmentioning
confidence: 99%
“…Hence, it is strongly desired to develop a computeraided diagnosis system to support clinical practitioners. Many existing works using deep learning have been proposed to automatically diagnose thoracic diseases for chest X-ray images in recent years and achieve remarkable progress, such as disease classification [2,3], abnormality detection [4,5], chest X-ray segmentation [6,7], disease prediction [8,9]. Among various computer-aided diagnosis tasks for chest X-ray images, our work aims to address the disease classification task.…”
Section: Introductionmentioning
confidence: 99%